Controlling the Functional Properties of Oligothiophene Crystalline Nano/Microfibers via Tailoring of the Self‐Assembling Molecular Precursors. (21st June 2018) - Di Maria, Francesca; Zangoli, Mattia; Gazzano, Massimo; Fabiano, Eduardo; Gentili, Denis; Zanelli, Alberto; Fermi, Andrea; Bergamini, Giacomo; Bonifazi, Davide; Perinot, Andrea; Caironi, Mario; Mazzaro, Raffaello; et al.
Abstract: Oligothiophenes are π‐conjugated semiconducting and fluorescent molecules whose self‐assembly properties are widely investigated for application in organic electronics, optoelectronics, biophotonics, and sensing. Here an approach to the preparation of crystalline oligothiophene nano/microfibers is reported based on the use of a "sulfur overrich" quaterthiophene building block, T4S4 , containing in its covalent network all the information needed to promote the directional, π–π stacking‐driven, self‐assembly ofY‐T4S4‐Y oligomers into fibers with hierarchical supramolecular arrangement from nano‐ to microscale. It is shown that when Y varies from unsubstituted thiophene to thiophene substituted with electron‐withdrawing groups, a wide redistribution of the molecular electronic charge takes place without substantially affecting the aggregation modalities of the oligomer. In this way, a structurally comparable series of fibers is obtained having progressively varying optical properties, redox potentials, photoconductivity, and type of prevailing charge carriers (from p‐ to n‐type). With the aid of density functional theory (DFT) calculations, combined with powder X‐ray diffraction data, a model accounting for the growth of the fibers from molecular to nano‐ and microscale is proposed. Abstract : The change of the aryl groups attached to the inner quaterthiophene core—promoting the directional, π–π‐stacking‐driven, self‐assembly into fibers —enables an unprecedented tuning of various properties within a set of structurally comparable crystalline, electroactive, self‐assembled nano/microfibers. In particular, changes in polarity of major charge carriers from p‐type to n‐type and light emission from visible to NIR are described.